A note on modelling with measures: Two-features balance equations - Michael Böhm; Martin Höpker (Mathematical Biosciences and Engineering)
In this note we explain by an example what we understandby a balance situation and by a balance equation in termsof measures. The latter ones are an attempt to start modelling of (not only)diffusion-reaction or mass-conservation scenarios in terms of measuresrather than by derivatives and other rates. By means of three examples this concept is extended to two-features (=two-traits-) balance situations, which, e.g., combine features like aging andphysical motion in populations or physical motion and formation of polymers by means of a single model equation.